Differential detection scheme for distributed MIMO systems in fast fading channel - Dong-dong DOU; Jun-bo LIU; Da-ming WANG; Zhao-xun LI (Tongxin xuebao)
In the fast fading distributed MIMO system,it is difficult to keep the channel fading coefficient unchanged in adjacent space-time blocks due to the rapid changed state information,which leads to the traditional distributed MIMO differential detection scheme is not suitable any.Aiming at this matter,an improved differential detection scheme was proposed.By recombining space-time codes which were differential modulated by phase,this differential detection scheme reduced the influence from fast fading channels at the cost of larger processing delay and additional transmission power.Theoretical analysis and some computer simulation results show that this scheme can improve the BER performance remarkably in fast fading channels compared with the existing the conventional differential space time detection.